1994
DOI: 10.1002/ajh.2830450206
|View full text |Cite
|
Sign up to set email alerts
|

Topical thrombin and acquired coagulation factor inhibitors: Clinical spectrum and laboratory diagnosis

Abstract: Topical bovine thrombin preparations are used extensively in cardiovascular, neurosurgical, and otolaryngologic procedures. Patients who are treated with these topical thrombin preparations may develop antibodies to bovine coagulation factors that may cross-react with the endogenous human clotting proteins. We have identified four patients with acquired factor inhibitors following exposure to topical thrombin at Duke University Medical Center and summarize these cases in addition to 13 patients previously repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 22 publications
(2 reference statements)
3
85
0
1
Order By: Relevance
“…However, the overlapping APC resistance results between controls and patients makes it difficult to apply this concept to individual patient care [41]. Patients have been reported to develop autoantibodies against factor V after exposure to bovine thrombin leading to APC resistance, with subsequent thrombosis of unclear etiology [42][43][44]. One study has also observed APC resistance (as measured by endogenous thrombin potential without dilution into factor V-deficient plasma) in unselected patients with untreated hematological malignancies, which may contribute to the increased risk of venous thrombosis observed in these patients [45].…”
Section: Apc Resistance Without Factor V Leidenmentioning
confidence: 99%
“…However, the overlapping APC resistance results between controls and patients makes it difficult to apply this concept to individual patient care [41]. Patients have been reported to develop autoantibodies against factor V after exposure to bovine thrombin leading to APC resistance, with subsequent thrombosis of unclear etiology [42][43][44]. One study has also observed APC resistance (as measured by endogenous thrombin potential without dilution into factor V-deficient plasma) in unselected patients with untreated hematological malignancies, which may contribute to the increased risk of venous thrombosis observed in these patients [45].…”
Section: Apc Resistance Without Factor V Leidenmentioning
confidence: 99%
“…[9] Three other patients presented serious bleeding and received a specific treatment without anticoagulant. [10][11][12] All of these 4 patients evolved favorably. The remaining six patients were treated with heparin (LMWH or unfractionated heparin) during the initial phase followed by anti-vitamin K or oral anticoagulants.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Granulomatous foreign body reactions and excessive fibrotic reactions may lead to catastrophic sequelae, particularly when the agents have been used within the abdominal cavity. Cases of appendicitis, 8 small bowel obstruction 9 and caseating peritoneal granulomas 10 have been described.…”
Section: Case Presentationmentioning
confidence: 99%